Implementation of School (GLS) Literation Action SMK Negeri Bali mandala and SMK Negeri 1 Sawan - Luh Meilani Novita Sari (Journal of Psychology and Instruction, 2019)
The aims of this study are to describe (1) The implementation of school literacy action (TISL), and (2) supporting elements of TISL at SMK Negeri Bali Mandara and SMK Negeri 1 Singaraja. The type of this study is qualitative qualitative. The subject of this research was the teachers and the students of SMK Negeri Bali Mandara and SMK Negeri 1 Singaraja. The object of this study was the implementation of school literacy action and supporting elements of the implementation school literacy action. The data was analyzed through several steps: reduction, classification, and description, interpretation, and conclusion. The result showed that SMK Negeri Bali Mandara were able to implemented 11 literacy-related activities meanwhile SMK Negeri 1 Singaraja only achieved 10. The supporting elements of school literacy action are (1) School Literacy Committee (SLC), (2) TISL Program, (3) The availability of infrastructure such as library and reading corner, (4) Student, teacher, and parent involvement, (5) Budget quota to reinforce infrastructure. Based on the result of this study, the school authority should be maintain maintenance of the facilities, the teachers should be collaborate with the students in implementing this literacy program. The students should be interested in reading and writing through literacy program.